Pengaruh Komitmen Organisasi Pemerintah Desa, Sistem Pengendalian Internal, dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Keuangan Desa (Studi Empiris Pada Desa Se-Kabupaten Jepara) - Agustiyana Lailatus Sholikhah; Hadi Sasana; Nuwun Priyono (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to analyze the effect of village government organizational commitment, internal control system, and the use of information technology on village financial management accountability (empirical study in villages throughout Jepara Regency). The research method used is a quantitative research method with primary data obtained from questionnaires measured using a Likert scale. The population in this study were villages in the local government area of ​​Jepara Regency, totaling 184 villages from 16 sub-districts. The sampling method in this study was using probability sampling in the form of simple random sampling. Determination of the number of samples in this study was carried out using a statistical method in the form of the Slovin formula. The results of this study state that partially the organizational commitment of the village government does not affect the accountability of village financial management, partially the internal control system has a positive effect on the accountability of village financial management, partially the use of information technology has an effect on positive to the accountability of village financial management, and simultaneously the commitment of village government organizations to the internal control system, and the use of information technology have a positive effect on village financial management accountability.